Zodiacal exoplanets in time – X. The orbit and atmosphere of the young 'neptune desert'-dwelling planet K2-100b. Issue 1 (8th April 2020) - Gaidos, E; Hirano, T; Mann, A W; Owens, D A; Berger, T A; France, K; Vanderburg, A; Harakawa, H; Hodapp, K W; Ishizuka, M; Jacobson, S; Konishi, M; et al.
ABSTRACT: We obtained high-resolution infrared spectroscopy and short-cadence photometry of the 600–800 Myr Praesepe star K2-100 during transits of its 1.67-d planet. This Neptune-size object, discovered by the NASA K2 mission, is an interloper in the 'desert' of planets with similar radii on short-period orbits. Our observations can be used to understand its origin and evolution by constraining the orbital eccentricity by transit fitting, measuring the spin-orbit obliquity by the Rossiter–McLaughlin effect, and detecting any extended, escaping the hydrogen–helium envelope with the 10 830 -Å line of neutral helium in the 2s 3 S triplet state. Transit photometry with 1-min cadence was obtained by the K2 satellite during Campaign 18 and transit spectra were obtained with the IRD spectrograph on the Subaru telescope. While the elevated activity of K2-100 prevented us from detecting the Rossiter–McLaughlin effect, the new photometry combined with revised stellar parameters allowed us to constrain the eccentricity to e < 0.15/0.28 with 90/99 per cent confidence. We modelled atmospheric escape as an isothermal, spherically symmetric Parker wind, with photochemistry driven by ultraviolet radiation, which we estimate by combining the observed spectrum of the active Sun with calibrations from observations of K2-100 and similar young stars in the nearby Hyades cluster. Our non-detection (<5.7 m Å) of a transit-associated He i line limits mass-loss of a solar-composition atmosphere through a T ≤ 10000 K wind to <0.3 M⊕  Gyr −1 . Either K2-100b is an exceptional desert-dwelling planet, or its mass-loss is occurring at a lower rate over a longer interval, consistent with a core accretion-powered scenario for escape.